Principles of fare constructions for passengers transportation in surban and local trains - Pinchuck, O. P. (Science and Transport Progress, 2011)
In the article the principles of generating tariffs for the suburban and regional passenger transportations with a possibility of determining the profitableness of a specific train are proposed.